Stressful Working Conditions and Union Dissatisfaction - Lowe, Graham; Northcott, Herbert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1995)
This paper examines the relationship between stressful working conditions, social support at work, employee distress, and union members' (dis)satisfaction with their union. It might be assumed that under stressful working conditions, unionized workers would turn to their union to seek better working conditions and would have a positive orientation toward their union. However, it is also possible that stressful working conditions and distressed, alienated employees will become dissatisfied not only with their job but also with their union. The data for this study corne from a survey of unionized postal workers employed by Canada Post Corporation in Edmonton in 1983.